Proteomic analysis of body wall and coelomic fluid in Sipunculus nudus. Issue 111 (April 2021) - Cao, Yupo; Lu, Xuli; Dai, Yaping; Li, Yahui; Liu, Fei; Zhou, Wei; Li, Jihua; Zheng, Baodong
Abstract: In order to make clear the protein compositions of Sipunculus nudus and investigate its immune-related proteins, proteomic analysis was performed on body wall and coelomic fluid of Sipunculus nudus . A total of 1659 proteins were identified, and 539 proteins were differentially expressed in the coelomic fluid compared to those in the body wall, of which 415 proteins were up-regulated while 124 proteins were down-regulated. Gene Ontology (GO) analysis showed that the GO terms involved in the two parts of Sipunculus nudus were similar, with metabolic processes, catalytic activity and cell occupying the top categories of biological process, molecular function and cellular component, respectively. KEGG pathway analysis showed that 49 pathways in body wall and 48 in coelomic fluid were mapped respectively, and these pathways were mainly related to cellular processes, environmental information processing, genetic information processing and metabolism. The COG analysis showed that 757 proteins from body wall and 889 from coelomic fluid were classified into 26 COG categories, respectively. Pfam annotation revealed the mainly immune-related proteins contained in Sipunculus nudus, such as insulin-like growth factor binding protein, catalase, basement membrane proteoglycan, titin. Our research provides the first proteomic information of Sipunculus nudus, which contributes to the study of functional proteins in Sipunculus nudus and is of great significance for the application of Sipunculus nudus in functional foods and medicines. Graphical abstract: Image 1 Highlights: Proteomic was used to investigate the biological functions of Sipunculus nudus proteins. A total of 1373 and 1566 proteins were respectively identified in BW and CF. The identified proteins were mainly involved in catalytic activity and metabolic processes. A solid foundation was laid for studying the functional proteins in Sipunculus nudus .